2015
DOI: 10.1088/0004-637x/808/2/139
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR PopIII-LIKE STELLAR POPULATIONS IN THE MOST LUMINOUS LyαEMITTERS AT THE EPOCH OF REIONIZATION: SPECTROSCOPIC CONFIRMATION

Abstract: Faint Lyman-α (Lyα) emitters become increasingly rarer towards the re-ionisation epoch (z ∼ 6−7). However, observations from a very large (∼ 5 deg 2 ) Lyα narrow-band survey at z = 6.6 (Matthee et al. 2015) show that this is not the case for the most luminous emitters, capable of ionising their own local bubbles. Here we present follow-up observations of the two most luminous Lyα candidates in the COSMOS field: 'MASOSA' and 'CR7'. We used X-SHOOTER, SINFONI and FORS2 on the VLT, and DEIMOS on Keck, to confirm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
467
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(498 citation statements)
references
References 119 publications
29
467
2
Order By: Relevance
“…We note that this is also consistent with recent work suggesting that a massive cluster of Population III stars, an alternative explanation for the origin of CR7 (e.g. Sobral et al 2015;Visbal et al 2016; see also Johnson 2010), is dubious since it is unknown how a sufficiently high mass of Population III stars could be assembled rapidly enough to explain the observed extremely bright emission (e.g. Hartwig et al 2016;Yajima & Khochfar 2016;Xu et al 2016;Visbal et al 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We note that this is also consistent with recent work suggesting that a massive cluster of Population III stars, an alternative explanation for the origin of CR7 (e.g. Sobral et al 2015;Visbal et al 2016; see also Johnson 2010), is dubious since it is unknown how a sufficiently high mass of Population III stars could be assembled rapidly enough to explain the observed extremely bright emission (e.g. Hartwig et al 2016;Yajima & Khochfar 2016;Xu et al 2016;Visbal et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The extremely bright Lyman α emitter known as CR7 is an intriguing candidate for a high-redshift quasar that may be powered by accretion onto a DCBH (Sobral et al 2015). Recent modeling efforts have demonstrated that a nearby galaxy may well have produced a high enough level of LW radiation to induce the formation of a DCBH in this galaxy and that the nebular emission could be explained by an accreting BH with a mass consistent with formation as a DCBH (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First, offsets between the sites of star formation and regions of Lyα emission have been reported in the literature (e.g. Sobral et al 2015). Moreover, density fluctuations (or the presence of sub-halos) in the CGM could account for the observed clumps.…”
Section: Photoionization From Galaxy Gmentioning
confidence: 90%
“…The origin of He iiλ1640 emission in galaxies has been a matter of investigation, possibly produced by massive stars both in the local Universe (e.g., Szécsi et al 2015;Gräfener & Vink 2015) and at high-redshift (e.g., Cassata et al 2013;Sobral et al 2015;Pallottini et al 2015). He iiλ1640 detection is generally A51, page 10 of 13 associated with AGN activity, but it has also been reported that He iiλ1640 associated with no C ivλ1550 is a possible feature in star-forming galaxies at z ∼ 3 (Cassata et al 2013).…”
Section: Is Ion2 An Agn?mentioning
confidence: 99%